2007
DOI: 10.1007/s10800-007-9410-5
|View full text |Cite
|
Sign up to set email alerts
|

Potential and current density distributions along a bipolar electrode

Abstract: Potential and current density distributions were modelled and measured for an electrochemical cell with a bipolar electrode. The dimension of the bipolar electrode in the direction of current flow was extended, to enable experimental determination of the electrode potential and the local current densities at various positions inside the electrolyte and in the electrode body. The experimental results showed that the most active regions of the bipolar electrode are located at the ends of the bipolar electrode fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…In the 8e arrangement, the two outer electrodes served as the forcing electrodes and the six inner electrodes behaved as bipolar electrodes. 30 The bipolar electrodes are not connected to the electric source and form highly conductive stripes on the microchannel wall with opposite electric charges localized at the stripe ends.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 8e arrangement, the two outer electrodes served as the forcing electrodes and the six inner electrodes behaved as bipolar electrodes. 30 The bipolar electrodes are not connected to the electric source and form highly conductive stripes on the microchannel wall with opposite electric charges localized at the stripe ends.…”
Section: Methodsmentioning
confidence: 99%
“…One being that all six internal electrodes behave like bipolar electrodes with the electrochemical charge transfer localized predominantly at the edges. 30 Above each bipolar electrode, the droplet can lose a part of its original charge. The bipolar electrode becomes itself charged.…”
Section: A Oscillatory Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…As is known, however, a significant risk of this approach is a decrease in process efficiency. This is caused by the existence of by-pass or shunt currents [43] which are influenced by the system geometry, number of bipolar electrodes, electrolyte conductivity, electrode reaction kinetics and the conductivity of the electrode material. Careful optimization of the cell parameters was, therefore, ensured by means of mathematical modeling of the local potential and current density distribution.…”
Section: Microstructured Cell Designmentioning
confidence: 99%
“…The presence of gases in the outlet manifolds was considered, Tafelian kinetics was adopted at the electrodes and uniform current distributions along the electrodes were assumed. Furthermore, Kodým et al [4] reported experimental and theoretical results of potential and current distribution in a bipolar system. The special configuration of the electrochemical reactor allowed for the simulation of the current distribution along the electrode thickness and the identification of the electrode ends as the most active regions of the bipolar electrode.…”
mentioning
confidence: 99%